Efficacy and safety of hepatic arterial infusion chemotherapy combined with fruquintinib and tislelizumab for patients with microsatellite stable colorectal cancer liver metastasis following failure of multiple-line therapy - Zheng, Kanglian; Zhu, Xu; Xu, Liang; Cao, Guang; Niu, Chuanxin; Yan, Xiaoluan; Xu, Da; Liu, Wei; Bao, Quan; Wang, Lijun; Wang, Kun; Xing, Baocai; et al. (Frontiers in Oncology, 2024)
The prognosis of microsatellite stable (MSS)-colorectal cancer liver metastasis (CRCLM) which failed from multi-line therapy remains dismal. The aim of this study is to evaluate the efficacy and safety of hepatic arterial infusion chemotherapy (HAIC) plus fruquintinib and tislelizumab (HAIC-F-T treatment) for MSS-CRCLM which failed from multiple-line therapy. From February 2021 to June 2023, 45 patients with MSS-CRCLM after failure of multiple-line therapy who received HAIC combined with fruquintinib and tislelizumab (HAIC-F-T triple treatment) were enrolled. The combination therapy included HAIC regimens with oxaliplatin and 5-fluorouracil or irinotecan, oxaliplatin, and 5-fluorouracil on days 1-2, intravenous tislelizumab (200 mg) before HAIC on day 1, and oral fruquintinb (3 mg/d) on day 3-21, every 4 weeks. Overall survival (OS) and progression-free survival (PFS) were estimated using the Kaplan-Meier method. The follow-up ended on June 22, 2024, with a median follow-up time of 17.5 months. The objective response rate was 42.2%, and the disease control rate was 82.2%. The median OS was 15.3 months (95% confidence interval [CI]:12.634-17.966), and the median PFS was 7.5 months (95% CI:5.318-9.682). The independent risk factors related to worse OS were previous PD-1 immunotherapy (P = 0.021) and the number of HAIC-F-T triple treatment cycles of ≤ 2 (P = 0.007). The incidence of grade 3 or higher adverse events (AEs) was 20%, with the most frequent grade 3 or higher AEs being abdominal pain (3/45, 6.7%). In conclusion, HAIC combined with fruquintinib and tislelizumab may be an alternative salvage treatment for patients with MSS-CRCLM who failed multiple-line therapy.